MEMBANGUN DIGITAL CUSTOMER EXPERIENCE PADA GENERASI MILENIAL - Simamora, Agatha; Pratama Sulistyo, Andy (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2023)
The theory of consumer experience has long been invented by schoolars, even starting in the 1990s. The disclosure of this theory began in the 1990s in a traditional and conventional business context. Businesses are still faced with purchases and consumers on the sidelines, face-to-face meetings, and direct interaction, and the consumer can still see and try the product in person. The development of business in the Internet era has brought about a variety of technologies and digital media, one of which is the online store. The conditions of online business are very different from those of conventional and traditional business. Consumers cannot interact directly and face-to-face; they cannot see and try the product directly. Then, what about the purchasing experience experienced and felt by today's consumers? This research looks at every element of the customer experience at every stage of consumer purchasing decisions. Research is qualitative research with the method of group discussion focused on questions that have been structured. The study involved 10 sources selected according to certain criteria, one of which was the age range of the millennial generation. The findings reveal new elements in consumer experience in the digital age by referring to consumer experiences presented in the 1990s.